Information System for Village Fund Assistance Management in Kelurahan Rantau Jaya Udik Sukadana, Lampung Timur - Kusmiya, Eri Yuliawati (Institute of Computer Science (IOCS), 2023)
The development of technology that is increasingly increasing encourages human nature to utilize and use technology as well as possible. The emergence of this research aims to make it easier for the Rantau Jaya Udik village office in managing village fund assistance and in taking village fund assistance. The problem that often occurs in the village village of Rantau Jaya Udik is that the financial management of village funds does not accommodate the allocation of village funds in accordance with village needs, such as unclear and often changing finances that are not in accordance with village development planning, and in the distribution of village funds often there is a discrepancy with the village development plan which is located in Sukadana District, East Lampung Regency. For that we need a computerized information system that is able to overcome existing obstacles and problems. The method used in making this system is to use the RUP (Rational Unified Process) method. Then the design is done by making Usecase Diagrams of the proposed system, Activity Diagrams, Sequence Diagrams and Class Diagrams, and applied to a system for making Web-based information systems. This study resulted in an information system for managing village funds for the village office of Rantau Jaya Udik.